2023
DOI: 10.5194/acp-23-2579-2023
|View full text |Cite
|
Sign up to set email alerts
|

Satellite remote sensing of regional and seasonal Arctic cooling showing a multi-decadal trend towards brighter and more liquid clouds

Abstract: Abstract. Two decades of measurements of spectral reflectance of solar radiation at the top of the atmosphere and a complementary record of cloud properties from satellite passive remote sensing have been analyzed for their pan-Arctic, regional, and seasonal changes. The pan-Arctic loss of brightness, which is explained by the retreat of sea ice during the current warming period, is not compensated by a corresponding increase in cloud cover. A systematic change in the thermodynamic phase of clouds has taken pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 125 publications
0
0
0
Order By: Relevance
“…Similarly to the ice water path, also the zonally averaged liquid water path increases with temperature in all three groups in the polar regions (Figure 9c). This is consistent with the findings of Lelli et al (2023) who report an observed trend to brighter and more liquid clouds in satellite measurements over the Arctic. In contrast to the ice water path, the lowest ECS group shows the highest sensitivity in the Arctic latitude belt.…”
Section: Cloud Liquid and Ice Water Path 265supporting
confidence: 93%
“…Similarly to the ice water path, also the zonally averaged liquid water path increases with temperature in all three groups in the polar regions (Figure 9c). This is consistent with the findings of Lelli et al (2023) who report an observed trend to brighter and more liquid clouds in satellite measurements over the Arctic. In contrast to the ice water path, the lowest ECS group shows the highest sensitivity in the Arctic latitude belt.…”
Section: Cloud Liquid and Ice Water Path 265supporting
confidence: 93%
“…Changes in cloud cover, especially low-level liquid containing clouds, would affect the amount of solar radiation reaching the surface. Previous studies have presented evidence for positive and negative trends in low cloud cover for the Arctic region (Boccolari and Parmiggiani, 2018;Jenkins and Dai, 2022;Lelli et al, 2023;Sviashchennikov and Drugorub, 2022;Wang et al, 2021). Increases in cloud cover would affect the amount of radiation received at the surface, which would affect ODEs mainly in March when radiation is lower compared to the later spring months.…”
Section: Discussionmentioning
confidence: 95%
“…The data record covers the period 1982-2016 and was funded by the European Space Agency (ESA) as part of the ESA Climate Change Ini-tiative (CCI) programme. Although the morning (AM) sensor series was available, it was found that only the afternoon (PM) series has the radiometric stability needed for trend studies (Lelli et al, 2023). The second satellite record is produced by the National Oceanic and Atmospheric Administration (NOAA) and the National Centers for Environmental Information (NCEI) from the High Resolution Infrared Radiation Sounder (HIRS) instruments on board the NOAA and MetOp (Meteorological Operational) satellites (Zhang et al, 2021).…”
Section: 7mentioning
confidence: 99%
“…The trends are 0.138 ± 0.017, 0.037 ± 0.010, and 0.106 ± 0.009 W m −2 yr −1 for BEST COMB, CMIP6/w, and CMIP6/s, respectively. The uncertainty ranges account for the standard deviation of the trends, using the bootstrap method of Lelli et al (2023). The fluxes are averaged over the Arctic area north of 66 • N and account for the extended winter period DJFM.…”
Section: Pan-arctic Atmospheric Energy Transport Convergencementioning
confidence: 99%